Geologists of Russian origin in Latin America - Tchoumatchenco, Platon (2018)
We describe here the life and career of geologists who beyond their nationality (Russian, Ukrainian, Tatar, German, etc.), were born on the territory of the Russian Empire, the Soviet Union or the Russian Federation and their descendants that became geologists, all of whom lived and worked in Latin-American countries (where Spanish and Portuguese languages prevail). We include also geologists from USSR who worked temporary in some countries of Latin America and left contributions to geology in form of publications.